Assessing Resident Safety Culture in Nursing Homes: Using the Nursing Home Survey on Resident Safety - Castle, Nicholas G. (J Patient Saf, 2010)
OBJECTIVES: To examine the overall responses of nursing home staff to a newly developed nursing home specific survey instrument to assess patient safety culture (PSC) and to examine whether nursing home staff (including Administrator / Manager, Licensed Nurse, Nurse Aide, Direct Care Staff, and Support Staff) differ in their PSC ratings. METHODS: Data were collected in late 2007 through early 2008 using a survey administered to staff in each of 40 nursing homes. In four of these nursing homes the responses of different staff were identified. The Nursing Home Survey on Patient Safety Culture (NHSPSC) was used to assess 12 domains of the PSC and identify differences in PSC perceptions between staff. RESULTS: For the 40 nursing homes in the sample, the overall facility response rate was 72%. For the four nursing homes of interest, the overall facility response rate was 68.9%. The aggregate NHSPSC scores, using all staff types for all survey items, show that most respondents report a poor PSC. However, Administrators / Managers had more positive scores than the other staff types (p<0.05) across most domains. CONCLUSIONS: Staff in nursing homes generally agree that PSC is poor. This may have a significant impact on quality of care and quality of life for residents.